Internal Performance of an Integrated Supply Chain: Does Flexibility Matter? - Wijaya, Aida; Gumilar, Ivan; Rahmana, Arief; Khalid, Nadeem (ExcelingTech, 2019)
The prime objective of the currents study, is to investigate the link between supply chain integration (SCI) and Internal Supply chain performance (ISCP). Apart of investigation the impact on internal performance of integrated supply chain, the current study is also interested in investigating the mediating role of Supply Chain flexibility (SCF) in the relationship between SCI and supply chain internal performance ISCP. The structural equation modeling which a twostep process i.e. inner model assessment and outer model assessment is and is an upgraded version of multiple regression is used to answer the research questions. The current study has used the AMOS to analyze the data collected from production managers of Indonesian manufacturing firms. The findings of the study have revealed the fact that SCI has significant impact on the internal supply chain performance (ISCP). The SCF has significantly mediated the relationship between SCI and ISCP. The study will be helpful for policy makers in researcher in understanding the issues related to supply chain, its integration, flexibility, and internal performance.